2019
DOI: 10.1136/rapm-2018-000023
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of postoperative analgesia on systemic inflammatory response and postoperative cognitive dysfunction after femoral fractures surgery: a randomized controlled trial

Abstract: Background and objectivesTo investigate the possible effect of postoperatively applied analgesics—epidurally applied levobupivacaine or intravenously applied morphine—on systemic inflammatory response and plasma concentration of interleukin (IL)-6 and to determine whether the intensity of inflammatory response is related to postoperative cognitive dysfunction (POCD).MethodsThis is a randomized, prospective, controlled study in an academic hospital. Patients were 65 years and older scheduled for femoral fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 38 publications
1
36
1
1
Order By: Relevance
“…It is mainly used for surgical anesthesia. General anesthesia acts on the central nervous system and affects the release of buttons and the connection of receptors: general anesthesia plays an important role in the activation of GABA and midazolam glycine receptors in the central nervous system and may prolong hippocampal neuronal activity [22]. It has an obstructive effect on the central choline working system and the N-methyl-D-asparagine (NMDA) receptor function; it can regulate the neuronicotine receptor, serotonin working receptor, and adrenaline working receptor.…”
Section: Principles Of General Anesthetics General Anesthesiamentioning
confidence: 99%
“…It is mainly used for surgical anesthesia. General anesthesia acts on the central nervous system and affects the release of buttons and the connection of receptors: general anesthesia plays an important role in the activation of GABA and midazolam glycine receptors in the central nervous system and may prolong hippocampal neuronal activity [22]. It has an obstructive effect on the central choline working system and the N-methyl-D-asparagine (NMDA) receptor function; it can regulate the neuronicotine receptor, serotonin working receptor, and adrenaline working receptor.…”
Section: Principles Of General Anesthetics General Anesthesiamentioning
confidence: 99%
“…In addition, an in vitro study demonstrated that inhaling an anesthetic might result in the activation of caspases and cell apoptosis, and also increase the production of Aβ, which can finally influence the course of Alzheimer’s disease . POCD is considered a severe disease, particularly in elderly people, because this condition significantly lengthens the time for rehabilitation . POCD can prolong hospital course, hinder disease recovery, raise postoperative complications and lower the quality of life after discharge .…”
mentioning
confidence: 99%
“…Postoperative cognitive dysfunction (POCD) is a debilitating surgical complication (Smith et al, 2018), characterized by symptoms such as memory deterioration, loss of concentration, attention-deficit disorder, mental disorders, and even personality change (Newman et al, 2001). Studies showed that POCD can occur after all types of surgery, not just after heart surgery (Edipoglu & Celik, 2019;Holmgaard et al, 2019;Kristek et al, 2019). The reported incidence of POCD is 26% within a few weeks which decreased to 10% 3 months after noncardiac surgery (Brown & Purdon, 2013).…”
Section: Introductionmentioning
confidence: 99%